Study Of Thyroid Profile In Different Trimesters Of Pregnancy - Lamichhane, Anit (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Thyroid disorders and dyslipidemia are frequent during pregnancy, which are associated with complications for both the mother and the fetus. Hence, this study aims to evaluate thyroid function test and its association with dyslipidemia in pregnancy.Method: This laboratory-based cross-sectional study was carried out in Manmohan Memorial Teaching Hospital, Kathmandu, Nepal. A total of 200 participants; where 100 pregnant and 100 non pregnant women were included in the study. Pregnant women were further subdivided into 1st, 2nd and 3rd trimester groups. Thyroid Profile and Lipid profile were estimated. Student t-test, one way ANOVA, and Pearson’s correlation were applied.Findings: The findings of the study revealed that the level of TSH was significantly (p